THE EFFECTS OF INVESTMENT OPPORTUNITY SET (IOS) AND CORPORATE-FINANCING ON DIVIDEND PAYOUT POLICY (A Study on Automotive and Components Companies Listed in Indonesia Stock Exchange Period 2009-2011) - Jaquelina N.L Sarmento (Jurnal Administrasi Bisnis, 2014)
Studi ini dilakukan untuk menganalisa pengaruh parsial dan simultan dari Investment Opportunity Set (IOS) dan pengukuran dari pendanaan-perusahaan yaitu Debt to Equity Ratio (DER) dan Debt Maturity Ratio (MAT) terhadap Dividend Payout Ratio (DPR). Jenis penelitian adalah penelitian kuantitatif dan teknik pengambilan sampel adalah purposive sampling. Terdapat 30 perusahaan sampel dari perusahaan otomotif dan komponen yang terdaftar di BEI selama 2009-2011 yang diuji dalam program SPSS (Statistical Package for the Social Science). Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi berganda. Penelitian ini juga menggunakan uji-t untuk menguji pengaruh parsial dan uji-F untuk menguji pengaruh simultan dengan level signifikansi 5%. Dengan menggunakan regresi berganda sebagai metode analisis, hasil dari uji F menunjukkan bahwa IOS, DER, dan MAT secara simultan berpengaruh terhadap DPR. Sementara itu, hasil dari uji t menunjukkan bahwa hanya variabel DER yang memiliki pengaruh signifikan terhadap DPR. Variabel independen lainnya yaitu IOS dan MAT tidak memiliki pengaruh yang signifikan terhadap DPR. Kata kunci: Investment Opportunity Set (IOS), Debt to Equity Ratio (DER), Debt Maturity Ratio (MAT), and Dividend Payout Ratio (DPR) Abstract The purpose of this study is to analyze the partial and simultaneous effects of Investment Opportunity Set (IOS) and the measurement of corporate-financing namely Debt to Equity Ratio (DER) and Debt Maturity Ratio (MAT) on Dividend Payout Ratio (DPR). The type of the research is quantitative research and the sampling technique is purposive sampling. There are 30 sample companies from automotive and components companies listed in IDX during the period of 2009-2011 examined in SPSS (Statistical Package for the Social Science). The analysis technique used in this research is multiple regression analysis. This research also uses t-test in order to examine the partial effects and F-test in order to examine the simultaneous effect with 5% level of significance. By using multiple regression as the method analysis, the result of F-test shows that IOS, DER, and MAT simultaneously have effect on DPR. Meanwhile, the result of t-test shows that only DER variable that has negative significant effect on DPR. The other variables namely IOS and MAT do not have significant effect on DPR. Keywords: Investment Opportunity Set (IOS), Debt to Equity Ratio (DER), Debt Maturity Ratio (MAT), and Dividend Payout Ratio (DPR)